Bodies and Bites: a medical school program that teaches anatomy, physiology, and nutrition to elementary school kids - Butterfield, Kimberly; Wesley, Mary; Carvalho, Helena; Holt, Emily; Toy, Serkan; Powell, Courtney; Trinkle, David; Rau, Kristofer K. (Frontiers in Public Health, 2024)
Undergraduate medical students who participate in community outreach programs gain a multitude of benefits that impact not only their professional development but also the well-being of the communities they serve. At the Virginia Tech Carilion School of Medicine (VTCSOM), students have the opportunity to volunteer in the “Bodies and Bites” program at the West End Center for Youth, an after-school educational center that serves K-12 children in Roanoke, Virginia. The purpose of Bodies and Bites is to teach elementary school children in 2nd to 5th grade how their bodies work and how to keep them healthy through good nutrition and exercise. All sessions are led by VTCSOM medical students and graduate students from our partnering academic institution, the Fralin Biomedical Research Institute (FBRI). Each week, the children and Health Professions students explore a different topic related to human anatomy and physiology using anatomical models, small group discussions, and hands-on activities. At the end of each session, the participants create a healthy snack related to the day’s topic. The overall goal of the present study was to assess the perception of the Bodies and Bites program from the view of our student volunteers, and the 4th and 5th graders who attend the West End Center. Now in its 6th year, Bodies and Bites continues to be popular as a voluntary program among our Health Professions students, and is well received by the West End Center and the elementary school children they serve. Our students and community mutually benefit from this program, with the former having an opportunity to briefly disengage from the rigors of their studies while gaining valuable skills in science communication and inspiring children to pursue fields in Science, Technology, Engineering, Math, and Medicine (STEMM), and the latter having fun while learning about their bodies and discovering ways to improve their health.